STRATEGI KEPALA SEKOLAH DALAM PENINGKATAN MUTU DI MTsN NEGERI 2 RUKOH BANDA ACEH - Ema Sulastri (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2014)
The principal strategy is the most decisive factor in the success of quality improvement in schools. Principal's leadership was instrumental in the successful implementation of quality improvement in schools. A good quality of education will improve the quality of school graduates so as to increase the educational success in the future. This study aims to describe the principal strategy for quality improvement. The study used a qualitative approach with descriptive methods. Data collection techniques used were observation, interview and documentation studies . Location Research is MTsN 2 Rukoh which became subject of research was the Principal and Teachers. While the technique of data analysis is data reduction, data display and conclusion. The results of the study are as follows: 1) the principal strategy in the planning of quality improvement is to involve all teachers in the school. Quality planning is done at the beginning of the year and the beginning of the semester . Quality planning as well as a forum for deliberation involving MGMPs teachers. 2) Implementation of quality improvement undertaken by the principal by making training and post training teachers, empower talent development school facilities and student interest. implement the recitation of the Quran in the morning, noon salat in congregation, providing training to students tajhid corpse. Conduct training of practicing and reading Quran correctly to students. 3) Strategies principals in supervising the quality control is in the range of weekly and monthly. The school principal use in the supervision of teaching quality control technique using two kinds of techniques, namely individual and group techniques.Â Kata kunci: Strategi kepala sekolah, mutu pendidikan